Proposal of a mobile application : notification of certificates of judicial deposits - Andrade Arenas, Laberiano Matías (2023)
In the last years, it has been seen how the number of judicial processes in Peru is affected by inefficiency or lack of agility for their attention and due process. Due to the digital transformation that has arisen with the use of IT, it has been necessary to choose to restructure the processes in the judicial systems by prioritizing the activities within each one to adapt to the new context that exists. Thus, given this need, this research arises, which aims to implement a mobile application to optimize the management of notifications in the delivery of judicial deposit certificates in the Judicial Branch. In order to effectively carry out this mobile application, the Mobile-D agile methodology has been chosen, which has 5 phases that start from the exploration phase to the testing phase. In addition, Figma was used as a tool for prototype design. In this way, the objective of improving the notification system for judicial deposits was achieved. After applying expert judgment to 5 specialists, it was obtained that the developed application, according to 5 criteria, had the following percentages of acceptance: design at 65%, the interface at 73.3%, performance at 75%, 95% integration and 91.6%.